Type III Fetal Sacrococcygeal Teratoma: Prenatal Diagnosis, Delivery and Postnatal Course - Ay, Orhan; Şahin, Fethiye; Bahçeci, Pelin; Madenci, Hasan; Acar, Ali (Acta medica Lituanica, 2026)
Background: Sacrococcygeal teratoma (SCT) is the most common congenital neoplasm in fetuses and newborns. Altman Type III lesions may be difficult to diagnose and manage prenatally because of their marked intrapelvic extension. Materials and Methods: A 24-year-old primigravida woman was referred at 20 weeks of gestation after routine ultrasonography revealed a sacrococcygeal mass extending into the abdomen. Prenatal evaluation included ultrasonography, fetal magnetic resonance imaging, and chromosomal microarray analysis. The pregnancy was managed by a multidisciplinary team with serial fetal surveillance. Results: Imaging demonstrated a predominantly cystic lesion consistent with Altman Type III SCT. During follow-up, bilateral fetal hydronephrosis, gestational diabetes mellitus, and mild polyhydramnios developed. At 38 weeks, an elective cesarean section was performed. On postnatal day 4, total tumor resection with coccygectomy was successfully completed. Histopathology confirmed a mature teratoma. At 6 months, persistent hydronephrosis remained under follow-up, with no documented recurrence. Conclusions: Accurate prenatal imaging, close surveillance, multidisciplinary planning, and timely postnatal surgery are essential for favorable outcomes in Type III fetal SCT.